Political pamphlets and sermons from Wales, 1790-1806 - Löffler, Marion; Jenkins, Bethan Mair, 1979- (Wales and the French Revolution., 2014)
This pioneering volume for the first time highlights Wales's contribution to the 'French Revolution debate' that unfolded in the pamphlet literature of the British isles after 1789. An in-depth essay reviews the Welsh political pamphlets and sermons of the period focusing on the debates between religious Dissenters, Methods and the Church; radicals and loyalists; as well as pacifists and patriotic war supporters. Its second part presents annotated editions of five important Welsh political pamphlets with full translation, thus making them accessible to an English-speaking audience for the first time. Among the illustrations is the first political Welsh-language cartoon.